CP40 from Corynebacterium pseudotuberculosis is an endo-β-N-acetylglucosaminidase. Issue 1 (December 2016) - Shadnezhad, Azadeh; Naegeli, Andreas; Collin, Mattias
Abstract Background C. pseudotuberculosis is an important animal pathogen that causes substantial economical loss in sheep and goat farming. Zoonotic infections in humans are rare, but when they occur they are often severe and difficult to treat. One of the most studied proteins from this bacterium, the secreted protein CP40 is being developed as a promising vaccine candidate and has been characterized as a serine protease. In this study we have investigated if CP40 is an endoglycosidase rather than a protease. Results CP40 does not show any protease activity and contains an EndoS-like family 18 of glycoside hydrolase (chitinase) motif. It hydrolyzes biantennary glycans on both human and ovine IgGs. CP40 is not a general chitinase and cannot hydrolyze bisecting GlcNAc. Conclusion Taken together we present solid evidence for re-annotating CP40 as an EndoS-like endoglycosidase. Redefining the activity of this enzyme will facilitate subsequent studies that could give further insight into immune evasion mechanisms underlying corynebacterial infections in animals and humans.